South Park : v.4 - Parker, Trey.; Schneider, Eliza; Gracie Lazar; Isaac Hayes; Mary Kay Bergman; Matt Stone; Mona Marshall; Trey Parker (USA Comedy Central, 1997)
South Park is an animated series featuring four foul-mouthed 3rd graders, Stan, Kyle, Kenny and Cartman. The show is set in the Colorado town of South Park where weird things keep happening, whether its being abducted by aliens or avoiding Kyle's little brother Ike. The show is based on the short film by Trey Parker and Matt Stone, ""The Spirit of Christmas"".
Follows the misadventures of four irreverent grade-schoolers in the quiet, dysfunctional town of South Park, Colorado.
Language(s): English
Subtitle(s): Turkish
Keywords: Comedy; Animation -- Tv Series